Erratum: ZHANG, B.S., ZHANG, F. & CHEN, P. (2011) Species of the genus Mallinella Strand, 1906 (Araneae: Zodariidae) from Hainan Island, China. Zootaxa, 2986, 55–62. - Zhang, B. S.; Zhang, F.; Chen, P. (Zootaxa, 2011)
(Erratum)